Pathogenic effect of four isolates of Beauveria bassiana (Bals.) Vuill. (Hyphomycetos) on larvae of Bombyx mori (L.) (Lepidoptera: Bombycidae) under laboratory conditions. - LOPEZ-NUNEZ, JUAN CARLOS (Revista Colombiana de Entomología, 1994)
The art for rearing insects that produce silk and the utilization of the latter is known as Sericulture. Bombyx mori (L.) is an insect that produces the largest amount of silk. This insect is attacked by protozoa, bacteria, viruses, and fungi. Once the coffee berry borer Hypothenemus hampei (Ferrari) was established in Colombia, some research was conducted in order to control this pest by using entomopathogenic fungi. As a result of this strategy, there is some risk related to the effect of spraying the fungi on coffee plantations, just near the place where the mulberry crop is established, since the latter, is the only food consumed by the silkworm throughout its life span. The main aim of this experiment was to determine the differences in pathogenicity of four isolates of B. bassiana to the silkworm. The isolates Bb-9002, Bb9022, Bb-9105, and Bb-9107 fromH. hampei, Nephotettiv cincticeps (Ulher), Perileucoptera coffeella (Guérin - Méneville) and B. mori, respectively, were used. Groups of 50 larvas (five replicates) were inoculated with a concentration of 1 x107 conidia ml, of each isolate, respectively. During the evaluation, the mortality caused by a virus, which produces the «Nuclear Polyhedrosis» (VNP) was registered. Larvae inoculated with the isolate Bb-9107 showed the highest percentage of mortality (10%), followed by the isolate Bb9105. Both isolates were obtained from lepidoptera. The highest percentage of viral mortality observed was also on larvae infected with the isolate Bb-9107.